2017
DOI: 10.2151/sola.13a-002
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Stratospheric Warmings and Anomalous Upward Wave Activity Flux

Abstract: Abrupt breakdowns of the polar winter stratospheric circulation such as sudden stratospheric warmings (SSWs) are a manifestation of strong two-way interactions between upward propagating planetary waves and the mean flow. The importance of sufficient upward wave activity fluxes from the troposphere and the preceding state of the stratospheric circulation in forcing SSWlike events have long been recognized. Past research based on idealized numerical simulations has suggested that the state of the stratosphere m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
129
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(150 citation statements)
references
References 34 publications
18
129
0
Order By: Relevance
“…In describing the onset stage (37 to 23 days prior) to sudden warming events, Limpasuvan et al () noted that the zonal flow is anomalously strong and the vortex anomalously pole centered. Birner and Albers () also noted that the vortex was anomalously strong prior to those sudden stratospheric deceleration events (see their definitions) that were preceded by lower tropospheric wave events (see, e.g., their supporting information Figure S1). The results shown in Figure seem to at least confirm that from the vortex‐centered view of CAVE‐ART, the vortex is anomalously strong prior to many sudden warming events.…”
Section: Applications and Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In describing the onset stage (37 to 23 days prior) to sudden warming events, Limpasuvan et al () noted that the zonal flow is anomalously strong and the vortex anomalously pole centered. Birner and Albers () also noted that the vortex was anomalously strong prior to those sudden stratospheric deceleration events (see their definitions) that were preceded by lower tropospheric wave events (see, e.g., their supporting information Figure S1). The results shown in Figure seem to at least confirm that from the vortex‐centered view of CAVE‐ART, the vortex is anomalously strong prior to many sudden warming events.…”
Section: Applications and Resultsmentioning
confidence: 94%
“…Our vortex strength definition, combined with other CAVE‐ART diagnostics, could be useful for identifying preconditioned states of the vortex prior to weak vortex events, including major and minor sudden warming disturbances. Perhaps more importantly, diagnostics from CAVE‐ART could assist in further understanding the physics through which the stratospheric vortex strengthens and weakens in such extreme ways by helping to reconcile views based on wave mean flow interactions of upward propagating waves (e.g., Limpasuvan et al, , ; Matsuno, ; Nishii et al, ), nonlocal wave effects (e.g., Esler & Matthewman, ; Harnik, ; Matthewman & Esler, ; Plumb, ; Shaw & Perlwitz, ), and internal stratospheric control (e.g., Birner & Albers, ; de la Cámara et al, ; Hitchcock & Haynes, ; Scott & Polvani, , ) with the dynamics in the frame of reference of the vortex itself.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, de la Torre et al () found that while WACCM reproduced the observed frequency of SSWs, they tend to last longer and vortex splits tend to occur earlier in the winter than observed. de la Cámara et al () used WACCM to show that SSW development depends on the stratospheric state, as has been shown using observations (Birner & Albers, ). Zonal asymmetries in WACCM meteorology and phenomenology associated with breaking planetary waves (PWs) at mesospheric altitudes are realistic (e.g., Chandran et al, ; France et al, ; France & Harvey, ; Greer et al, ; Sassi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some results that suggest that internal stratospheric dynamics may also play a role during SSWs. Recently, Birner and Albers (2017) showed that only 25% of SSWs were associated to anomalously large tropospheric wave events, while the remaining 75% of SSWs have wave fluxes that are anomalous only in the stratosphere. Recently, Birner and Albers (2017) showed that only 25% of SSWs were associated to anomalously large tropospheric wave events, while the remaining 75% of SSWs have wave fluxes that are anomalous only in the stratosphere.…”
Section: Introductionmentioning
confidence: 99%